Impacto dos investimentos em tecnologia de informação no desempenho financeiro das indústrias brasileiras - Longo, Luci (2014)
The results obtained enable us to state that the industries that most invested in Information Technology (IT) in the period of 2001-2011 had higher growth in their operating revenue and more effective operating results, compared with industries that invested less in the same period. According to the proposed model for the companies studied, an increase of 7% was found within two years in operating profit for every 1% in IT investments. Noteworthy is the purpose of the research to identify and analyze the impacts of expenditures and investments in information technology on the financial performance of Brazilian industries, and for that, I used a research model that used accounting-financial metrics and indicators of IT use as well as the combination of statistical analysis techniques. Moreover, the investigation deepens and broadens the discussion on the evaluation of IT investments and how to measure its impact on the organizational performance. The study population was composed of Brazilian companies, which were publicly traded, from the industrial sector, with active stocks at BOVESPA, totaling 119 companies. Through a survey, additional data were obtained related to expenditures and investments in IT, the semi-structured questionnaires were sent directly to the Chief Information Officer (CIO). These efforts in collecting primary data, gave the possibility of obtaining a fairly significant sample, with 63 industries, namely 53% of the population. After collection, the data analysis was developed through three steps: (1) Factor Analysis (FA) for selection of performance factors, which at the end of the process resulted in twelve variables for the research model, (2) Cluster Analysis (CA) that showed three distinct groupings of companies for their features and performance, and (3) Multiple Regression Model which adopted the Generalized Method of Moments (GMM), a dynamic econometric model, satisfying the requirements of the Arellano-Bond (1991) model. It is noted that the proposed model could address in a methodologically proper way the spurious correlations and allowing the identification of ‘the lag effect', in other words, IT investments in two previous periods, (IGTIt-2) impacted in current Operating Income (ROPt). Furthermore, it was found that other variables of profitability and liquidity impacted in this result, also adopting lag variables. The main variable of IT research, IGTI is calculated through the sum of expenditures and annual IT investments (OPEX/CAPEX), divided by the annual net Operating Revenue. For future research, there is the possibility of seeking evaluation measures by types (categories) of IT investment, aiming at deepening the analysis of performance impacts by sector (in each investment) and the cluster analysis, making use of the analysis model of this research.